Luminescence and energy transfer mechanisms in photo-thermo-refractive glasses co-doped with silver molecular clusters and Eu3+. Issue 40 (12th October 2020) - Marasanov, Dmitriy V.; Mironov, Leonid Yu.; Sgibnev, Yevgeniy M.; Kolesnikov, Ilya E.; Nikonorov, Nikolay V.
Abstract : Silver molecular clusters were synthesized in photo-thermo-refractive glasses using the Na + –Ag + ion exchange technique followed by heat treatment. Abstract : Silver molecular clusters were synthesized in photo-thermo-refractive glasses using the Na + –Ag + ion exchange technique followed by heat treatment. Comprehensive study of cluster emission reveals the presence of spectrally separated fluorescence and phosphorescence with nanosecond and microsecond lifetime. Co-doping of glasses with Eu 3+ was shown to results in quenching of cluster luminescence caused by energy transfer. The monitoring of silver cluster luminescence quantum yield and lifetime in the presence of Eu 3+ indicates the presence of two different mechanisms of energy transfer. The first one affects the decay kinetics of cluster fluorescence and manifests at long distances, while the second one leads to static quenching of cluster emission at shorter distances and becomes prominent at higher doping Eu 3+ concentration.